Passive Coping Associations With Self-Esteem and Health-Related Quality of Life in Youth With Inflammatory Bowel Disease - Reed, Bonney; Rea, Kelly E.; Claar, Robyn Lewis; van Tilburg, Miranda A. L.; Levy, Rona L. (Frontiers in Psychology, 2021)
Pediatric patients with inflammatory bowel disease (IBD) may experience chronic stress related to disease symptoms and treatment, with negative consequences to their health-related quality of life (HRQOL). Lower HRQOL among pediatric patients with IBD has been associated with worse disease-related symptoms and psychological functioning, while higher HRQOL has been associated with more adaptive coping with disease symptoms and treatment. In addition, patients’ self-esteem may impact the selection and use of coping strategies through global cognitions about their abilities and perceived competence. The current study seeks to extend existing research on HRQOL in youth with IBD by examining cross-sectional associations among self-esteem and passive coping strategies. Youth ages 9 to 18 with IBD (n=147) rated their HRQOL using a disease-specific measure, typical strategies used to cope with pain or GI symptoms, and their general self-esteem. Mediation analyses were performed using regression-based techniques and bootstrapping. Results indicated that greater self-esteem was positively associated with HRQOL but negatively associated with passive coping. Controlling for disease activity, age, and gender, significant indirect effects were found in the relation between self-esteem and HRQOL through passive coping. Multiple mediation analyses using the three passive coping subscales found that self-esteem was indirectly associated with HRQOL through its effects specifically on catastrophizing as a passive coping strategy. Results suggest that pediatric patients’ general self-esteem can impact their HRQOL through passive coping and specifically, maladaptive cognitions (e.g., catastrophizing). Interventions aimed at addressing both self-esteem and catastrophizing as a passive coping strategy may offer promise for improving HRQOL in youth with IBD.